INCREASING INFORMATION AND TECHNOLOGICAL COMPETENCE IN TRAINING FUTURE PRIMARY CLASS TEACHERS - Pardayev Asror Ikromovich; Z.M.O‘rinboyev, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, it is based on the fact that the formation of innovative competence of future teachers is an urgent pedagogical problem, and the possibilities of using effective forms and methods for the formation of innovative competence of future teachers, formal and informal assessment methods adopted by teachers are considered.